Relation Between Self Efficacy and Quality of Life in Type II Diabetes Mellitus Patient in Sukabumi District - Mustopa Saepul Alamsah (Jurnal EduHealth, 2023)
The target of the study was patients with type II diabetes mellitus. Data were analyzed using univariate analysis to test each variable and bivariate test to test the relationship between variables. Result: Self-efficacy in patients with Type 2 Diabetes Mellitus in the Working Area of Puskesmas in Sukabumi District is in the insufficient category. Quality of life in Type 2 Diabetes Mellitus patients in the Working Area of Puskesmas in Sukabumi Regency is in the moderate category. Self-efficacy has a significant relationship (p value=0.001) with the quality of life of Type 2 Diabetes Mellitus patients in the Working Area of Puskesmas in Sukabumi District.